A STUDY ON THE SYNTACTIC FEATURES OF ENGLISH AND VIETNAMESE LYRICS ADOPTING THE FUNCTIONAL GRAMMAR APPROACH - CLAUSE AS A MESSAGE - Ngô Thị Phước Yên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Adopting the Functional grammar approach, the reseach paper considers the clause as a message. That is, the reseach aims to study on the Thematic structure, which gives the clause its character as a meassage. Using a descriptive method to classify, describe and analyze the Theme – Rheme in English and Vietnamese in terms of semantics and pragmatics, the study provides a systematic view on the Thematic structure in both languages. The data of the study were collected from articles, books, Master Thesis and the internet in both English and Vietnamese. The data were classified, described and analyzed qualitatively and contrastively to yield more precise information on how thematic structure is formed and how it helps to emphasize, highlight, confirm, etc and makes a great impression on the audience. In addition, the study has been clearly presented based on 50 samples songs in English and another 50 Vietnamese songs, Hopefully, this research benefits the learners of English and Vietnamese translators and those who are interested in thematic structure in English as well as Vietnamese lyrics. Accordingly, some predicted problems in the language learning and teaching as well as practical and feasible implications are put forward in the hope they can benefit teachers of English and learners.